Review Pergeseran Fotografi Dari Sistem Konvensional ke Digital (Virtual Photoshoot) Pada Masa Pandemi COVID-19 - Adrian Permana Zen; Dyah Ayu Wiwid Sintowoko; Iqbal Prabawa Wiguna; Arfi Andrian; Gregorius Kresna Haga Ginting (JURNAL RUPA, 2021)
Virtual photoshoot is a new method in the development era of modern contemporary photography that was born due to the impact of COVID-19. This study finally tries to analyze the trend of virtual photoshoots as the use of photography technology during the Covid-19 pandemic. Virtual photoshoot is a development of photography. The method used in this research is a phenomenological approach regarding the use of online video call software in the process of shooting the object. The sample of this research is the photographic works of virtual photoshoot by Michael Fabians Cools when taking pictures using the sophisticated video call application. The results showed three main results, namely media, technical and aesthetic. In terms of media, research has found that the existence of social media such as Instagram can support the existence of a virtual photoshoot trend. Technically research, this virtual photoshoot implementation method is something new and has never happened before. The virtual photoshoot implementation method is applied in in-game screenshots and Google Street View, where virtual photoshoots offer a shooting process by taking pictures through an LCD monitor using video call software such as Zoom, Facetime, and Google Meet to bring up photo objects. Aesthetically, this study found that the results of photos from virtual photoshoots led to photography techniques that were not widely used before in conventional shooting, namely displaying the blur effect on photos using glasses or bottles. The blur effect that is usually produced through lens settings can also be produced with a glass or bottle.